Obesity and sleep disorders: A nationwide study of 1.3 million Israeli adolescents. Issue 6 (November 2020) - Geva, Neta; Pinhas-Hamiel, Orit; Frenkel, Hagay; Shina, Avi; Derazne, Estela; Tzur, Dorit; Afek, Arnon; Goldbart, Aviv D.; Twig, Gilad
Highlights: ⬢ Nationwide population study. ⬢ Increase in the prevalence of sleep disorders with increasing adolescent BMI. ⬢ More cases among males and a significantly stronger association in higher obesity classes. Abstract: Objectives: To assess the association between sleep disorders prevalence and obesity in Israeli adolescents. Methods: A nationwide, population-based, cross-sectional study of 1, 348, 817 Israeli adolescents (57% males) who were medically examined prior to military service between 1997 and 2015; height and weight were measured along with assessment of medical status at age 17.3⬰±⬰0.4 years. The diagnosis of a sleep disorder was made based on objective diagnostic criteria. The prevalence and odds ratio (OR) for a sleep disorder were computed across BMI subgroups and were adjusted for socio-demographic confounders. Results: Overall sleep disorders prevalence was 1.8:1000 (males) and 0.45:1000 (females), with a total of 1601 cases. There was a gradual increase in the odds ratio for sleep disorders with increasing BMI. Multivariable-adjusted ORs for sleep disorders were 1.29 (95% CI 1.10⬜1.52), 1.44 (1.18⬜1.75), 3.03 (2.32⬜3.96) and 3.38 (1.98⬜5.75) for overweight, obese class I, II and III, respectively (5 th ⬜49th BMI percentile was the reference). Results persisted in extensive sensitivity analyses including limiting the study sample to participants with unimpaired health. Conclusions: We found a higher prevalence of sleep disorders in males and a dose-dependent association between sleep disorders and adolescent BMI in both sexes. Our findings warrant clinical awareness among healthcare providers, given the rise in obesity in teenagers, and particularly in light of the obesity epidemic that we are experiencing in this era. Sleep related complaints should be actively screened in adolescents who suffer obesity.